An Archetype of Cognitive Innovation as Support for the Development of Cognitive Solutions in Smart Cities - Rodas Osollo, Jorge Enrique (Taylor & Francis, 2021)
This chapter presents a Cognitive Innovation Model that formalizes the basic components and the interactions between them for the establishment of a Cognitive Architecture (CA). The convenience of walking in the sense of achieving an archetype as support for the implementation of innovative intelligent solutions in Smart Cities and having the client as a means of convenient validation of the representation and processing of the knowledge expressed in the CA in comparison with those executed by humans in their daily activities.